ORGANISMS CAUSING URINARY TRACT INFECTION IN PEDIATRIC PATIENTS AT AYUB TEACHING HOSPITAL ABBOTTABAD - Qureshi, Azhar Munir (Journal of Ayub Medical College Abbottabad, 2005)
Background: Urinary tract infection (UTI) is common in pediatric practice and an important cause of morbidity and mortality in children. Infected urine stimulates an immunological and inflammatory response leading to renal injury and scarring, ultimately leading to end stage renal failure. The present study identifies the micro organisms causing urinary tract infection in children presenting with UTI at Ayub Teaching Hospital, Abbottabad. Methods: One hundred patients of either sex, ranging from neonatal period to fifteen years of age were studied at the Pediatric units of Ayub Teaching Hospital, Abbottabad. Urine colony count and culture were done on the suspected cases. Result: Urinary tract infection was common among females, except in the neonatal period. Escherichia coli was the most common organism isolated (71.0%), followed by Klebsiella (13%), Proteus (11%), Staphylococcus (4%) and Pseudomonas (1%). Proteus was isolated from the males only. Conclusion: UTI is a significant problem in the children and requires a large scale study at regular intervals in order to identify organisms from time to time and recommend prompt treatment to reduce UTI related morbidity and mortality in children. Keywords: Pyelonephritis, Colony count, Urine culture.